Glycogen Synthase Kinase-3: A New Therapeutic Target in Mood Disorders - ARICIOĞLU, FEYZA (KURE ILETISIM GRUBU A S, 2013)
Mood disorders, including major depressive disorder and bipolar disorder, are common and largely inadequately treated. Additionally, little is known about their etiologies. Glycogen synthase kinase-3 (GSK-3) is a serine/threonine protein kinase, interacting with many signaling pathways. In 1996, lithium was found to inhibit GSK-3 and this discovery led us to the possibility that impaired GSK-3 inhibition is related with mood disorders. In time, animal and human studies encouraged this finding. Evidence is reviewed that depression may be associated with impaired inhibitory control of GSK-3, and mania with hyperstimulation of GSK-3. Mood disorders may result in part from impairments in mechanisms controlling the activity of GSK-3 or GSK-3-regulated functions and substantial evidence supports the conclusion that bolstering the modulatory control of GSK-3 is an important component of the therapeutic actions of drugs used to treat mood disorders and that GSK-3 is a valid target for developing new therapeutic interventions. Future research should identify the causes of dysregulation of GSK-3 in mood disorders and the actions of GSK-3 that contribute to these diseases.
Keywords: Glycogen synthase kinase (GSK-3); mood disorders; lithium; brain-derived neurotrophic factor (BDNF); neuroinflammation; neuroplasticity; depression; PHOSPHORYLATION; INHIBITION; INSULIN; LITHIUM; ACTIVATION; GSK-3; INACTIVATION; MECHANISM; BRAIN; AKT